2006
DOI: 10.1016/j.mambio.2006.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Female aggression in red deer: Does it indicate competition for mates?

Abstract: Female-female competition over mates is often considered of minor importance, particularly in polygynous species. In red deer (Cervus elaphus), female-female aggression within harems during the breeding season has not been studied to date. Herein, we examined if oestrous female red deer in harems show elevated aggression rates, compared to when they are in harems but not in oestrous, and also when they are in foraging groups outside of the breeding season. Any increased levels of aggression involving oestrous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…3). Similarly, in some polygynous ungulates where males initially compete intensely for females, females that have entered estrus and need to mate rapidly compete for the attentions of defending males (57,58). Several studies of species where both sexes make large investments in their offspring have shown that the relative intensity of reproductive competition in the two sexes can be changed by manipulating resource availability and reversing sex differences in PRR (59,60).…”
Section: Sexual Selection In Femalesmentioning
confidence: 99%
“…3). Similarly, in some polygynous ungulates where males initially compete intensely for females, females that have entered estrus and need to mate rapidly compete for the attentions of defending males (57,58). Several studies of species where both sexes make large investments in their offspring have shown that the relative intensity of reproductive competition in the two sexes can be changed by manipulating resource availability and reversing sex differences in PRR (59,60).…”
Section: Sexual Selection In Femalesmentioning
confidence: 99%
“…Female competition over mating opportunities has been demonstrated in three other polygynous ungulates (red deer, Cervus elaphus, Bebié and McElligott 2006;topi, Damaliscus lunatus, Bro-Jørgensen 2002;saiga, Saiga tatarica tatarica, Milner-Gulland et al 2003). While females may be in competition for access to resources in a male's territory or home range, they may also be competing for the male's interest and limited sperm.…”
Section: Discussionmentioning
confidence: 99%
“…Overt aggression among females over mating opportunities has been observed in birds (Barnard and Markus 1989;Brown et al 1997;Nakamura 1998; reviewed by Slagsvold and Lifjeld 1994), amphibians (Bush and Dell 1997;Waights 1996), carnivores (Frame et al 1979;Rabb et al 1967;Rood 1980;Zimen 1975), ungulates (Bebié and McElligott 2006;Mackler and Dolan 1980), primates (reviewed by Niemeyer and Anderson 1983;Rendall and Taylor 1991), rodents (Bennett et al 1999), and fish (Brandtmann et al 1999). Competition for access to males may take the form of copulation harassment, or more subtly, females may restrict one another's access to the male by placing themselves close to him and displacing other females.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by the fact that aggressive acts by oestrous topi females increase their probability of mating (Bro-Jørgensen 2007b). A similar basis for female mate competition may also explain increased female aggression on fallow deer leks (Schaal 1987) and in oestrous red deer hinds (Bebie and McElligott 2006). Perhaps the strongest evidence that mate limitation can drive female competition is provided by a study on the saiga antelope (Saiga tatarica) which found that dominants aggressively excluded subordinates from mating, but only after poaching had biased the adult sexratio heavily towards females (Milner-Gulland et al 2003).…”
Section: Female Mate Competition In Ungulatesmentioning
confidence: 93%